The Interplay of Raloxifene and Sonochemical Bio-Oss in Early Maxillary Sinus Bone Regeneration: A Histological and Immunohistochemical Analysis in Rabbits - de Souza Santos, Anderson Maikon [UNESP] (2023)
The study aimed to assess the efficacy of using Raloxifene with ultrasonic processing to enhance Bio-Oss®, a bone graft substitute, for maxillary sinus bone height reconstruction. A total of 24 rabbit maxillary sinuses were distributed into three groups, each receiving different treatments: Bio-Oss® only, sonicated Bio-Oss, and sonicated Bio-Oss® with Raloxifene. Surgical procedures and subsequent histomorphometric and immunohistochemistry analyses were conducted to evaluate the bone formation, connective tissue, and remaining biomaterial, as well as the osteoblastic differentiation and maturation of collagen fibers. Results indicated that the sonicated Bio-Oss® and Bio-Oss® groups showed similar histological behavior and bone formation, but the Raloxifene group displayed inflammatory infiltrate, low bone formation, and disorganized connective tissue. The statistical analysis confirmed significant differences between the groups in terms of bone formation, connective tissue, and remaining biomaterial. In conclusion, the study found that while sonicated Bio-Oss® performed comparably to Bio-Oss® alone, the addition of Raloxifene led to an unexpected delay in bone repair. The findings stress the importance of histological evaluation for accurate bone repair assessment and the necessity for further investigation into the local application of Raloxifene. Future research may focus on optimizing bone substitutes with growth factors to improve bone repair.